Design and Development of Lecture Planning System in Informatics Study Program - Dyah Ayu Megawaty; Delsa Diana Saputri (PT. Tech Cart Press, 2023)
In everyday life, the existence of the internet is increasingly becoming an important part, including for students. Students can easily find information via the internet, but the function of the internet is not only that, especially for students, one of which is to arrange schedules, and find out grade information online. Strategy greatly influences students in undergoing lectures, it can even affect student achievement and graduation time. Therefore, this research produces a system for managing student strategies in lectures, for example scheduling lectures. The system developed is the Lecture Planning System. The development model used in this study is a procedural model in the form of the Extreme Programming (XP) application development methodology. Extreme Programming includes planning and analysis, so it is very helpful in determining learning and planning strategies. The results of the test obtained a score of 100% which indicates that this lecture planning application system is very feasible to use.